Pharmacognostical and Phyto-Chemical Evaluation of Bilvadi leha- An Ayurvedic Formulaton - Tiwari, Ramanand (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACTBilvadi leha is an Ayurvedic classical formulation described in the Sahasrayoga, Lehaprakarana-1. This compound contains Aegle marmelos (L) Corr. as chief ingredient. Pharmacognostical study of finished drug exposed the quality and genuineness of all the constituents of Bilvadi leha. Organoleptic features of Bilvadi leha were within the standard range. The pH value of Bilvadi leha is 6, Water soluble extract is 70.84%w/w, Alcohol soluble extract is 8.45%w/w, Ash value is 2.86%w/w, Loss of drying is 16.38%w/w.